2016
DOI: 10.1210/en.2016-1501
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and Energy Expenditure, But Not Feeding or Glucose Tolerance, Are Impaired in Young Kiss1r KO Female Mice

Abstract: Kisspeptin regulates reproduction via signaling through the receptor, Kiss1r, in GnRH neurons. However, both kisspeptin and Kiss1r are produced in several peripheral tissues, and recent studies have highlighted a role for kisspeptin signaling in metabolism and glucose homeostasis. We recently reported that Kiss1r KO mice display a sexually-dimorphic metabolic phenotype, with KO females displaying obesity, impaired metabolism, and glucose intolerance at 4 -5 months of age. However, it remains unclear when this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
69
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(74 citation statements)
references
References 28 publications
5
69
0
Order By: Relevance
“…[15][16][17] Here we further demonstrate that global Kiss1r KOs have lower body temperature and decreased BAT thermogenic gene expression, correlating with their lower metabolic rates. However, recent evidence from our group and others demonstrate that kisspeptin signaling is also important for non-reproductive processes, including metabolism and energy balance.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…[15][16][17] Here we further demonstrate that global Kiss1r KOs have lower body temperature and decreased BAT thermogenic gene expression, correlating with their lower metabolic rates. However, recent evidence from our group and others demonstrate that kisspeptin signaling is also important for non-reproductive processes, including metabolism and energy balance.…”
Section: Discussionsupporting
confidence: 65%
“…15,16 In addition to becoming obese, adult Kiss1r KO females also had increased adiposity, higher leptin levels, and substantially impaired glucose tolerance, both on standard chow and high-fat diets. Specifically, compared with WT littermates, global Kiss1r knockout (KO) female micelacking kisspeptin signaling in all tissues-displayed dramatically higher BWs beginning in early adulthood, weighing as much as 30% more than control females.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, studies with mice without a KP receptor (Kiss1r KO mice) showed that adult Kiss1r KO females remained on a standard chow diet revealed a marked increase in body weight compared to wild littermates . Following studies have shown that impaired kisspeptin signaling results in lower metabolism and energy expenditure, resulting in increased Kiss1r KO female mice adiposity . However, it is still unclear if increased levels of kisspeptin increase human energy expenditure.…”
Section: Discussionmentioning
confidence: 99%